Neuroprotective effects of Quercetin on radiation-induced brain injury in rats - Kale, Aydemir; Pişkin, Özcan; Baş, Yılmaz; Aydın, Bengü Gülhan; Can, Murat; Elmas, Özlem; Büyükuysal, Çağatay (Journal of radiation research, 2018)
Extensive research has been focused on radiation-induced brain injury. Animal and human studies have shown that flavonoids have remarkable toxicological profiles. This study aims to investigate the neuroprotective effects of quercetin in an experimental radiation-induced brain injury. A total of 32 adult male Wistar-Albino rats were randomly divided into four groups (control, quercetin, radiation, and radiation+quercetin groups, with eight rats in each group). Doses (50 mg/kg) of quercetin were administered to the animals in the quercetin and radiation+quercetin groups; radiation and radiation+quercetin groups were exposed to a dose of 20 Gy to the cranium region. Tissue samples, and biochemical levels of tissue injury markers in the four groups were compared. In all measured parameters of oxidative stress, administration of quercetin significantly demonstrated favorable effects. Both plasma and tissue levels of malondialdehyde and total antioxidant status significantly changed in favor of antioxidant activity. Histopathological evaluation of the tissues also demonstrated a significant decrease in cellular degeneration and infiltration parameters after quercetin administration. Quercetin demonstrated significant neuroprotection after radiation-induced brain injury. Further studies of neurological outcomes under different experimental settings are required in order to achieve conclusive results.